The infinite glade - Dashner, James, 1972- (Dashner, James, 1972- Maze cutter (Series), 2025)
The Infinite Glade is the final book of The Maze Cutter series, resolving long-unanswered questions of The Maze Runner world ... The group of descendants along with Old Man Frypan are forced to choose between risking their lives to share the painful truth of the evolving maze trials with the world, or escape the chaos with their lives and let the deepest darkest of secrets of the maze stay buried in the glade forever. -- Publisher.